In situ catalytic upgrading of oxygenated pyrolysis vapours from pyrolysis of sugarcane bagasse over metal oxides loaded HZSM-5 - Balasundram, Vekes; Khairunnisa, Kamarul Zaman; Norazana, Ibrahim; Rafiziana, Md. Kasmani; Ruzinah, Isha; Mohd. Kamaruddin, Abd. Hamid; Hasrinah, Hasbullahd (Springer, 2020)
The main objective of the current work is to study the performance of the NiO and Ce2O3 loaded HZSM-5 catalyst on the catalytic upgrading of oxygenated pyrolysis vapours from sugarcane bagasse into high-quality pyrolysis oil consisting of C6–C8 hydrocarbons. The experiments were performed at five different pyrolysis reaction temperatures (400, 450, 500, 550 and 600 °C) via in situ fixed bed reactor. The HZSM-5 was used as a support, while nickel oxides and/or cerium oxides were impregnated via incipient wetness impregnation method. The catalyst-to-biomass mass ratio was kept constant at 1:1 for all investigated samples. The results revealed that the NiO-Ce2O3/HZSM-5 catalyst has synergistic effects on upgrading the oxygenated pyrolysis vapours into higher contents of C6–C8 hydrocarbons (8.82%) in pyrolysis oil at 500 °C compared with other investigated catalysts.